Upright or inverted, entire or exploded: right-hemispheric superiority in face recognition withstands multiple spatial manipulations - Prete, Giulia; Marzoli, Daniele; Tommasi, Luca (PeerJ, 2015)
Background. The ability to identify faces has been interpreted as a cerebral specialization based on the evolutionary importance of these social stimuli, and a number of studies have shown that this function is mainly lateralized in the right hemisphere. The aim of this study was to assess the right-hemispheric specialization in face recognition in unfamiliar circumstances. Methods. Using a divided visual field paradigm, we investigated hemispheric asymmetries in the matching of two subsequent faces, using two types of transformation hindering identity recognition, namely upside-down rotation and spatial “explosion” (female and male faces were fractured into parts so that their mutual spatial relations were left intact), as well as their combination. Results. We confirmed the right-hemispheric superiority in face processing. Moreover, we found a decrease of the identity recognition for more extreme “levels of explosion” and for faces presented upside-down (either as sample or target stimuli) than for faces presented upright, as well as an advantage in the matching of female compared to male faces. Discussion. We conclude that the right-hemispheric superiority for face processing is not an epiphenomenon of our expertise, because we are not often exposed to inverted and “exploded” faces, but rather a robust hemispheric lateralization. We speculate that these results could be attributable to the prevalence of right-handedness in humans and/or to early biases in social interactions.
Keywords: Face matching; Exploded faces; Face-inversion effect; Divided visual field paradigm; Hemispheric asymmetries